Determination of Superior Aquaculture Commodities Around the Mandalika Special Economic Zone Through the Integration of LQ-AHP Analysis - Muhammad Nursan; Aeko Fria Utama FR; Ni Made Nike Zeamita Widiyanti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2025)
The potential of fishery resources around the Mandalika Special Economic Zone (KEK) has not been optimally utilized. This region possesses significant potential in aquaculture commodities that can support both industry and tourism. The selection of commodities should be based on the comparative advantages of each area to enhance productivity and sustainability of resources. The objective of this research is to identify the leading aquaculture commodities in the vicinity of the Mandalika Special Economic Zone in Central Lombok Regency. This study employs a descriptive approach. Data collection was conducted using survey techniques through interviews with 30 respondents selected via purposive sampling. Data analysis utilized Location Quotient (LQ) analysis and Analytical Hierarchy Process (AHP). The results indicate that the leading aquaculture commodities around the Mandalika Special Economic Zone include marine and pond aquaculture commodities, which are prominent in one district, while pond fishery commodities are identified as leading in all districts except for Pujut District. Cage fishery commodities are leading in two districts, and rice-fish farming is leading in eight districts. The priority leading marine aquaculture commodities are seaweed, lobster, pearls, and grouper. The priority leading freshwater aquaculture commodities are tilapia, catfish, gourami, and goldfish. Additionally, the priority leading brackish water aquaculture commodities are vannamei shrimp, tiger shrimp, and milkfish. These findings can serve as a foundation for determining policies in the planning and development for sustainable fisheries around the Mandalika Special Economic Zone.